The Body in Balance : Humoral Medicines in Practice - Peregrine Horden, Elisabeth Hsu (Berghahn Books, 2013)
The human body contains blood, phlegm, yellow bile and black bile. These are the things that make up its constitution and cause its pains and health. Health is primarily that state in which these constituent substances are in the correct proportion to each other [Greek metrios, ‘moderately, in due measure’], both in strength and quantity, and are well mixed.